PEMANTAUAN TUMBUH KEMBANG BALITA DI TAMAN POSYANDU DUSUN NGUMPUL - Dewi Triloka Wulandari (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
One of the opportunities for MSMEs to survive and grow during a pandemic is through a digital system. The Human Resource factor is the main key, starting from the business owner and the workforce in the owner's environment. Human Resource Management Training for Go Digital MSMEs aims to provide solutions for solving problems faced by the MSME sector, namely the skills of MSME itself in the field of Human Resource Management, especially in managerial skills, organizational management skills and the ability of MSME Human Resource to survive, be adaptive and resilience in the face of adversity during the pandemic. The methods for implementing this community service activity are lectures, tutorials, and discussions. The results achieved are as follows: (1) Participants are given knowledge and motivation to understand organizational management skills, managerial skills (Human Resource) at MSMEs; (2) The participants are given the opportunity to discuss problems and constraints related to MSME Human Resource management skills, MSME business strategies, and being a Go Digital MSME.